2021
DOI: 10.1016/j.molcel.2020.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Hyperosmotic stress alters the RNA polymerase II interactome and induces readthrough transcription despite widespread transcriptional repression

Abstract: Rosa-Mercado et al. report that hyperosmotic stress causes widespread transcriptional repression in human cells, yet DoGs arise regardless of the transcriptional response of their upstream genes. They find that the interaction between Pol II and Integrator is disrupted by hypertonicity and that knocking down the Integrator nuclease leads to DoG production. Highlights• Hyperosmotic stress triggers transcriptional repression of many genes.• DoG RNAs arise independent of the transcriptional level of their upstrea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(94 citation statements)
references
References 71 publications
9
71
0
Order By: Relevance
“…Disrupting snRNA formation by itself is unlikely to influence lytic infection as the rapid redirection of Pol II activity to viral genomes and transcriptional shutdown within the span of 8-12h would not be expected to alter the abundant pool of mature splicing factors, and most viral genes are unspliced late in infection when these termination defects are the greatest. Integrator also has direct roles in regulating protein-coding genes, and knockdown of its catalytic subunit recapitulates termination defects on a subset of host mRNAs disrupted during osmotic stress (64), though our previous work implicates ICP27-CPSF interactions as the primary determinant during HSV-1 infection (10). Work is ongoing to analyze the role of integrator in HSV-1 infection.…”
Section: Discussionmentioning
confidence: 92%
“…Disrupting snRNA formation by itself is unlikely to influence lytic infection as the rapid redirection of Pol II activity to viral genomes and transcriptional shutdown within the span of 8-12h would not be expected to alter the abundant pool of mature splicing factors, and most viral genes are unspliced late in infection when these termination defects are the greatest. Integrator also has direct roles in regulating protein-coding genes, and knockdown of its catalytic subunit recapitulates termination defects on a subset of host mRNAs disrupted during osmotic stress (64), though our previous work implicates ICP27-CPSF interactions as the primary determinant during HSV-1 infection (10). Work is ongoing to analyze the role of integrator in HSV-1 infection.…”
Section: Discussionmentioning
confidence: 92%
“…This conclusion is consistent with a report of global transcriptional repression in human cells exposed to heat shock ( Mahat et al, 2016 ). Global transcriptional down-regulation has also been seen in response to osmotic stress ( Rosa-Mercado et al, 2021 ). When we monitored nascent RNA synthesis by 4-TU incorporation in response to a variety of different environmental treatments ( Fig S6A ), we found that transcriptional down-regulation is a common response to environmental changes and stresses in budding yeast.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the integrator complex has been shown to associate with active enhancers and increases enhancer-promoter communication 77 . Decreased expression of INTS11, the catalytic subunit of the complex, promotes read-through transcription at polyadenylation sites and shifts alternative isoform expression towards the distal isoform 29,78 . This suggests that increased association of integrator at active enhancers could prevent read-through and could increase CPA activity.…”
Section: Discussionmentioning
confidence: 99%
“…Under physiological conditions it is currently difficult to disentangle the contribution of transcript production and transcript processing to the expression level of single-UTR genes. However, viral infection or osmotic stress impair transcript processing of cellular genes and lead to massive read-through transcription downstream of polyadenylation signals (PAS), thus illustrating the crucial contribution of transcript processing [26][27][28][29] . Moreover, point mutations or genetic variants that occur in PAS or in their surrounding sequence elements reveal the contribution of 3′ end processing activity to mRNA expression [30][31][32][33][34][35][36] .…”
Section: Introductionmentioning
confidence: 99%